MICROWAVE-ASSISTED HYDROTHERMAL SYNTHESIS OF Ni-DOPED SnO2 NANOPARTICLES AND THEIR USE AS CATALYSTS IN BIODIESEL PRODUCTION - De Sousa, D. G.; Oliveira, M. M.; Rangel, J. H. G.; Vasconcelos, J. S.; Longo, E. [UNESP] (Centro Federal Educacao Tecnologica Rio Grande Norte, 2017)
The high chemical stability and low cost of tin dioxide has been widely reported in the literature, as has its microwave-assisted hydrothermal synthesis. The use of heterogeneous catalysts in biodiesel synthesis has proved very promising, with conversion rates exceeding 80%. The purpose of this study was to synthesize Ni-doped SnO2 for application as a heterogeneous catalyst in the transesterification of vegetable oils. The powders were characterized by X-ray diffraction, Raman spectroscopy, scanning electron microscopy and N-2(g) adsorption/desorption using the Brunauer-Emmet-Teller (BET) method. The results revealed powders with nanometric agglomerates and high surface areas. Catalytic tests revealed an 80% retention factor and a decrease in the viscosity of babassu oil from 30.27 mm(2) s(-1) to 6.91 mm(2) s(-1), indicating that the synthesized catalyst can be used in the transesterification of vegetable oils.
Keywords: SnO2; microwave-assisted hydrothermal method; catalysts; biodiesel